State dependence, duration dependence and unobserved heterogeneity in the employment transitions of the over-50s - Lorenzo Cappellari; Richard Dorsett; Getinet Haile (University of Essex, Institute for Social and Economic Research (ISER), 2007)
This paper examines employment transitions among men and women in the UK aged between 50 and the state pension age. We begin by examining the issue of duration dependence, using standard duration models. We then use a fourth order Markov model to estimate quarterly transitions while allowing for potential endogeneity of initial conditions. The results reject exogeneity of initial conditions and show the importance of both duration dependence and state dependence. This implies there is the potential for any individual to become trapped in non-employment and, ideally, policy should intervene as soon as an individual begins a period of non-employment.
Keywords: 330